2013
DOI: 10.1542/peds.2013-1188
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Prenatal Weight Gain and Autism Spectrum Disorders

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Previous studies have found links between prepregnancy BMI and/or pregnancy weight gain and autism spectrum disorders (ASD) risk. Several contributing factors to BMI and pregnancy weight gain (ie, prematurity, advanced maternal age, parental education, and parity) overlap with established ASD risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
89
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(103 citation statements)
references
References 38 publications
8
89
3
3
Order By: Relevance
“…Rodriguez et al 19 found that excessive pregnancy weight gain among obese women increased children's ADHD risk. Bilder et al 38 reported an association between autism spectrum disorder and high pregnancy weight gain, independent of prepregnancy BMI; however, the latter study examined prepregnancy BMI as a continuous variable and did not assess interactions between prepregnancy BMI and weight gain.…”
Section: Discussionmentioning
confidence: 97%
“…Rodriguez et al 19 found that excessive pregnancy weight gain among obese women increased children's ADHD risk. Bilder et al 38 reported an association between autism spectrum disorder and high pregnancy weight gain, independent of prepregnancy BMI; however, the latter study examined prepregnancy BMI as a continuous variable and did not assess interactions between prepregnancy BMI and weight gain.…”
Section: Discussionmentioning
confidence: 97%
“…35,36 High maternal BMI related to conception shortly after a previous birth has also been hypothesized to explain the link between short IPI and ASD risk. Both maternal obesity 25 and gestational weight gain 22 have been reported to moderately increase risk of ASD. If a woman has gained substantial weight during her first pregnancy, the probability of high BMI at the start of the second pregnancy after a short IPI will be high.…”
Section: Discussionmentioning
confidence: 99%
“…These covariates have been previously reported to increase risk of ASD. [21][22][23][24][25][26][27][28][29] Change in maternal BMI between the 2 consecutive pregnancies (a proxy for maternal weight retention), birth weight, type of delivery, gestational age, and ASD status of the first child were also included in our analysis because they could possibly influence the length of IPI. We also explored the effect of intermediate variables preterm birth, low birth weight, and mode of delivery of second-born child on the measure of association between IPI and ASD.…”
Section: Covariatesmentioning
confidence: 99%
“…After excluding 156 duplicate studies and 828 irrelevant topics, 16 papers were identified on maternal obesity and ASD risk in offspring and were subjected to a detailed evaluation. Subsequently, seven studies were excluded because of irrelevant outcomes, including one study assessing maternal weight gain and ASD (Bilder et al 2013). Three reviews, and two news report without any eligible data were excluded as well.…”
Section: Literature Searchmentioning
confidence: 99%